2020
DOI: 10.1103/physrevb.101.125201
|View full text |Cite
|
Sign up to set email alerts
|

Nieh-Yan anomaly: Torsional Landau levels, central charge, and anomalous thermal Hall effect

Abstract: The Nieh-Yan anomaly is the anomalous breakdown of the chiral U(1) symmetry caused by the interaction between torsion and fermions. We study this anomaly from the point of view of torsional Landau levels. It was found that the torsional Landau levels are gapless, while their contributions to the chiral anomaly are canceled, except those from the lowest torsional Landau levels. Hence, the dimension is effectively reduced from (3+1)d to (1+1)d. We further show that the coefficient of the Nieh-Yan anomaly is the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 49 publications
7
32
0
Order By: Relevance
“…Due to the flexibility of condensed matter systems, there are no fundamental limitations to realize predictions that have remained hypothetical in the high-energy context. A fascinating example of such predictions is the Nieh-Yan anomaly [2][3][4][5][6][7][8] of chiral fermions in torsional spacetimes which has recently been proposed as a source of universal effects in condensed matter systems.…”
Section: Introduction-mentioning
confidence: 99%
See 4 more Smart Citations
“…Due to the flexibility of condensed matter systems, there are no fundamental limitations to realize predictions that have remained hypothetical in the high-energy context. A fascinating example of such predictions is the Nieh-Yan anomaly [2][3][4][5][6][7][8] of chiral fermions in torsional spacetimes which has recently been proposed as a source of universal effects in condensed matter systems.…”
Section: Introduction-mentioning
confidence: 99%
“…Until recently, physical consequences of the Nieh-Yan anomaly [2,3] have remained controversial due to the explicit appearance of the non-universal high-energy cutoff in physical predictions. However, several recent studies [4][5][6][7] have confirmed its universal character by identifying temperature as the appropriate substitute for the high-energy cutoff.…”
Section: Introduction-mentioning
confidence: 99%
See 3 more Smart Citations